RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS QUANTITATIVE ESTIMATION OF DILOXANIDE FUROATE AND ORNIDAZOLE IN TABLETS - Sivaprasad, P.; Yaswanth Kumar, S.; Kumar, A. Ashok (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To develop an accurate, precise and linear Reverse Phase High Performance Liquid Chromatographic (RP-HPLC) method for simultaneous quantitative estimation of Diloxanide furoate and Ornidazole in tablets and validate as per ICH guidelines. Methods: The optimized method uses a reverse phase C18 column, ZODIAC (250 X 4.6 mm; 5Î¼), mobile phase consisting of mixed phosphate buffer (KH2PO4 and K2HPO4): acetonitrile in the proportion of 30:70 v/v. The mobile phase was set at a flow rate of 1.0 ml/min and the volume injected was 20Î¼l for every injection. The detection wavelength was set at 279 nm. Results: The developed method resulted in Diloxanide furoate eluting at 4.293 min and Ornidazole at 3.34 min. Diloxanide furoate exhibited linearity in the range 90-210Î¼g/ml, while Ornidazole exhibited linearity in the range 60-140Î¼g/ml. The precision is exemplified by relative standard deviations of 0.97% for Diloxanide furoate and 0.3% for Ornidazole. Percentage Mean recoveries were found to be in the range of 98â€102, during accuracy studies. The limit of detection (LOD) for Diloxanide furoate and Ornidazole were found to be 8.80Âµg/ml and 6.68Âµg/ml respectively, while limit of quantitiation (LOQ) for Diloxanide furoate and Ornidazole were found to be 26.6Âµg/ml and 20.25Âµg/ml respectively. Conclusion: A simple, accurate, precise, linear and rapid RP-HPLC method was developed for simultaneous quantitative estimation of Diloxanide furoate and Ornidazole in Amicline plus tablets and validated as per ICH guidelines. Hence it can be used for the routine analysis of Diloxanide furoate and Ornidazole in tablets in various pharmaceutical industries.